Brief research report: Repurposing pentoxifylline to treat intense acute swimming–Induced delayed-onset muscle soreness in mice: Targeting peripheral and spinal cord nociceptive mechanisms - Borghi, Sergio M.; Zaninelli, Tiago H.; Saraiva-Santos, Telma; Bertozzi, Mariana M.; Cardoso, Renato D. R.; Carvalho, Thacyana T.; Ferraz, Camila R.; Camilios-Neto, Doumit; Cunha, Fernando Q.; Cunha, Thiago M.; Pinho-Ribeiro, Felipe A.; Casagrande, Rubia; et al. (Frontiers in Pharmacology, 2023)
Herein we pursued to determine the effect of pentoxifylline (Ptx) in delayed onset muscle soreness (DOMS) triggered by exposing untrained mice to intense acute swimming exercise (120 min), which, to our knowledge, has not been investigated. Ptx treatment (1.5, 4.5, and 13.5 mg/kg; i.p., 30 min before and 12 h after the session) reduced intense acute swimming-induced mechanical hyperalgesia in a dose-dependent manner. The selected dose of Ptx (4.5 mg/kg) inhibited neutrophils recruitment to the muscle tissue, oxidative stress and both pro- and anti-inflammatory cytokine production in the soleus muscle and spinal cord. Furthermore, Ptx treatment also reduced spinal cord glial cell activation. Concluding, Ptx targets peripheral and spinal cord mechanisms of DOMS to reduce pain.